ANALISIS USABILITY APLIKASI STREAMING MUSIK MENGGUNAKAN METODE SYSTEM USABILITY SCALE (SUS) - Taufik Agus Haryanto; Eka Rini Yulia (Jurnal Mahasiswa Sistem Informasi (JMSI), 2025)
Digital transformation has significantly changed the way people access and enjoy music. Music streaming platforms such as Spotify, YouTube Music, and Joox have become the primary choice for fulfilling audio entertainment needs quickly and flexibly. However, despite their popularity, each application still faces various user complaints related to the user experience, such as navigation issues, suboptimal features, and technical problems during offline playback. These issues are closely related to the usability aspect of each application. This study aims to evaluate the usability level of Spotify, YouTube Music, and Joox using the System Usability Scale (SUS) method, with data analysis performed using SPSS version 27. The research employed a quantitative approach with 100 respondents who are university students and active users of music streaming applications, selected through purposive sampling. The data were collected using a SUS questionnaire consisting of 10 statements. The results show that Spotify received the highest SUS score of 72.9 (“Good” category), followed by YouTube Music with 66.2, and Joox with 60.3 (both in the “OK” category). These findings indicate that, in general, the usability of the three applications is considered fairly good, although some aspects still require improvement.